Public Reactions to Indonesia's KRIS Policy: A Textual Network Analysis of Digital Legitimacy - Handojo, Pradono; Sudarsono Hardjosoekarto; Lydia Freyani Hayadi; Luayya, Lora; Lestari, Haifa Mayang; Amalia, Rianca (Journal of Public Health and Pharmacy, 2026)
ntroduction: Through the Presidential Regulation No. 59 of 2024 issued on May 8, 2024, the Government of Indonesia announced the elimination of the three-class inpatient service (Class 1, Class 2, and Class 3) in Indonesia. The regulation introduces a single standard inpatient service class (KRIS), effective July 1, 2025. This study analyzes the KRIS nursing policy by exploring comments on YouTube news reports during two distinct periods: before and after the policy announcement. It also evaluates the impact of public communication efforts by relevant institutions on public support for the policy. Methodologically, this study introduces a novel approach by integrating Textual Network Analysis (TNA) with digital legitimacy theory, offering a fresh lens to examine the construction of policy legitimacy in digital environments (YouTube). Methods: To address the first research question, TNA was conducted on comments on YouTube, capturing and analyzing public responses to KRIS policy-related news during both pre- and post-policy announcement periods. Data were collected using Communalityc and APIFY and analyzed using Gephi to visualize and generate word networks. To address the second research question, the authors quantified KRIS policy socialization videos and compared them with COVID-19 vaccination campaign videos, followed by a qualitative analysis. Results: The authors discover that public discourse and sentiment remained consistently negative both pre- and post-announcement. However, the focus of the discussion shifted from complaints about service quality and contribution burdens to more direct concerns over increased contributions and reduced benefits. Regarding the second research question, the authors conclude that compared to the COVID-19 vaccination campaign, efforts to promote the benefits of the KRIS policy have been relatively limited, with minimal engagement from the four government institutions involved. Conclusion: This study provides valuable insights into public discourse and sentiment regarding the Standard Inpatient Class (KRIS) policy, which is scheduled to take effect on July 1, 2025. The findings suggest that the government should strengthen its public engagement by adopting a more intensive, structured, and coordinated communication strategy—similar to that employed during the COVID-19 vaccination campaign—to boost public acceptance and enhance policy legitimacy.